Efficacy of autologous platelet-rich plasma injection in plantar fasciitis - Sharma, Pulkit; Gupta, Sanjeev; Sharma, Nikhil (International Journal of Research in Orthopaedics, 2026)
Background: Plantar fasciitis (PF) is the most common cause of chronic heel pain in adults, resulting from repetitive micro-trauma and degenerative changes of the plantar fascia. When conservative therapies fail, newer biological modalities such as platelet-rich plasma (PRP) are being explored. Methods: This prospective study was conducted in the Department of Orthopaedics, Government Medical College, Jammu, over a period of one year in collaboration with the blood bank. Thirty-eight patients with clinically diagnosed plantar fasciitis of ≥3 months’ duration, unresponsive to conservative therapy and with a baseline visual analogue scale (VAS) pain score >7, were included. PRP was prepared using the double-spin centrifugation method from 12 mL of autologous venous blood, and 2 ml of PRP were injected at the maximum tender point using the peppering technique. Patients were followed up at 1 week, 1, 2, 4, and 6 months. Pain relief was assessed using the VAS (0–10). Results: All 38 patients completed a 6-month follow-up. Mean baseline VAS was 8.68±0.47, which decreased to 7.21±1.63 at 1 month, 5.63±2.55 at 2 months, 5.42±2.16 at 4 months, and 5.03±2.43 at 6 months (p<0.05). The maximum improvement occurred by the second month and was sustained up to six months. Complete pain relief was achieved in 13.2% of patients by two months, while 78.9% experienced <50% pain reduction. No complications were reported. Conclusions: Autologous PRP injection is a safe, minimally invasive option for chronic plantar fasciitis, providing modest but sustained pain reduction.